Implementation of School Operational Assistance Program (BOS) - Sarif Hidayatullah; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
Implementation of school operational programs at SD Negeri Kebonsari 01 Candi District, Sidoarjo Regency can be realized if it is in accordance with the measurement of the implementation theory of Edward III, namely communication, disposition, bureaucratic structure and resources must be good. In this case, the implementation of the school operational assistance program carried out by SD Negeri Kebonsari 01, Candi Subdistrict, Sidoarjo Regency has been going well, but has experienced very minimal socialization barriers and there is also a lack of supervision in implementing it. The purpose of this research is to describe and analyze how the implementation of the school operational assistance program in SD Negeri Kebonsarii 01 Candi District, Sidoarjo Regency and to describe and analyze the obstacles in the implementation of the school operational assistance program. The method used in this research is descriptive qualitative method, data collection techniques in the form of observation, interviews, and documentation and analyzed by means of data collection, data presentation, data reduction and drawing conclusions. This study concludes that: from the four indicators of measuring the success of the implementation of the school operational assistance program at SD Negeri Kebonsari 01 which is said to be effective, it can be seen from the four indicators of successful implementation that have been achieved well. However, the obstacles faced were the lack of socialization to the guardians of students and also the lack of supervision of the implementation of school operational programs at SD Negeri Kebonsari 01.